Pemberdayaan Masyarakat Melalui Program CSR PT. PJB UBJOM PLTU Tenayan di Kelurahan Industri Tenayan - Tutut Pujayanti; Dadang Mashur (Penerbit Goodwood, 2021)
Purpose: This study aims to determine the implementation process as well as the driving and inhibiting factors of community empowerment through the Corporate Social Responsibility (CSR) program by PT. PJB UBJOM PLTU Tenayan in Industri Tenayan Village.Research Methodology: The method use in this research is descriptive qualitative with a case study approach.Results: The results of the implementation of each stage of empowerment have been realized, but are not optimal so that they have not been able to create community independence in the Tenayan Industrial Village. The awareness stage, by providing socialization, was carried out once and was attended by 30 residents of the Tenayan Industrial Village. In the capacity building stage, the community is given training in business management, group structure, and legality. Empowerment stage, giving seeds and cages. The Young Jaya Organic group consists of 7 members, 4 members showing good progress. The supporting factor is the support from stakeholders. The inhibiting factor is the unavailability of supporting technology in making media and processing results.Limitations: In this study, the authors did not get clear information regarding the division of tasks of each member in carrying out the activities of the Muda Jaya Organik Group.Contribution: Theoretically, this research can be used as reference material and a continuous comparison medium for future research that has the same topic and problems. So that it can lead to solving problems related to increasing public awareness and increasing the quality and quantity of production from the Young Jaya Organic Group.